Multiple solutions and stability analysis of magnetic hybrid nanofluid flow over a rotating disk with heat generation - Khashi'ie, Najiyah Safwa; Waini, Iskandar; Zainal, Nurul Amira; Hamzah, Khairum; Md Arifin, Norihan; Pop, Ioan (Semarak Ilmu, 2023)
This study highlights the hybrid Fe3O4-CoFe2O4/H2O ferrofluid flow and heat transfer with the effects of linear heat generation, magnetic field and suction on a rotating disk. Using the similarity transformation, the mathematical model is simplified and reduced to a similarity set of equations. The bvp4c solver is used for computational analysis as well as the stability analysis procedure. The present model is successfully validated with previous results, and also verified with the fulfillment of the asymptote profiles. Triple solutions are observed within a limited range of testing parameters. The flow progress of Fe3O4-CoFe2O4/H2O is reduced when some changes made by varying the magnetic and suction parameters while a reverse result is obtained for the third solution. Only the suction parameter boosts the thermal progress of Fe3O4- CoFe2O4/H2O. The stability analysis surprisingly shows that two of the solutions have positive smallest eigenvalues and align with the physical results.